KONSTRUKSI SEKSUALITAS DALAM KELUARGA (Studi terhadap Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan dan Kompilasi Hukum Islam) - Arifki, Arifki (Musawa Jurnal Studi Gender dan Islam, 2016)
This paper aims to explain the construction of the discourse of sexuality in Act No. 1 of 1974 on Marriage and the Compilation of Islamic Law. Discourse of sexuality is constructed, namely: the heterosexuality of marriage, polygamy, the rights and status of husband and wife, the status of the child, guardian, dowry, and matters relating to the relationship between men and women. The construction of the discourse of sexuality in the Marriage Act and the Compilation of Islamic Law cannot be separated from a conflict of interest, understanding gender, and the spirit of nationalism. The construction put women’s position under men. This has implications for discrimination and subordination of women’s sexuality and overrides the rights of the child. In addition, it also resulted in resistance against the Marriage Act and the Compilation of IslamicLaw, such as judicial review against them, and increased family problems that lead to divorce, in which women are more often than not the plaintiff.